Опыт и рекомендации по культивированию Ocimum basilicum L. в Донбассе - Кустова, О.К. (Промышленная ботаника, 2002)
Optimum conditions for growing the introduced Ocimum basilicum L. have been studied and defined in the Donetsk botanical gardens, Nat. Ukr. Acad. Sci. The outcome of the research has proved the natural-climatic conditions of the Donbass being favourable for cultivation of O. basilicum by sowing in the soil. To raise the quality of sowing materials of late ripe specimens and varieties O. basilicum it is expedient to employ the way of growing by seedlings. Green cutting enables to get additional plant material with certain traits and properties of a sort. On the basis of the data obtained there has been developed the guidance on basil’s and its varieties cultivation under the conditions of Donbass.